Dilihat Dari Perubahan Struktur Ekonomi Indonesia Dari Masa Ke Masa - Eki Indriyanti; Melkior Keleka Hayon; Muhammad Yasin (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
In the history of the Indonesian economy. Indonesia often experiences changes in its economic structure. Starting from the beginning of independence, namely the era of the first President of Indonesia, namely Soekarno, until now the Jokowi era. These changes often occur because the economic structure has not boosted the Indonesian economy and is considered unable to improve the welfare of the people. The economic structure is used to shows the composition or arrangement of economic sectors in an economy. Economic structure is also the implementation of existing economic systems with the aim of increasing the welfare of a country through economic development and growth of national income. The economic structure can be seen from four viewpoints, namely macro-sectoral review, financial review, state administration review, and bureaucratic decision-making review. The macro sectoral review and financial review are purely economic reviews, while the state review and decision-making bureaucratic review are political reviews. Dominant or reliable economic sectors can also mean sectors that make the largest contribution to the national product with high growth rates, which are characteristic of an economy.